Analysis of Lactobacillus plantarum Pa21 with surface anchored heterologous protein microencapsulated with polysaccharide - Md Sabidi, Sarah Safwah (2017)
Microencapsulation technology is retention of cells or active compounds within the microencapsulation matrix as a protection from harsh environments. The oral administration of microencapsulated probiotics carrying heterologous proteins through the Gastro intestinal tract (GIT) can be a novel approach for vaccine delivery. The peptidoglycan cell walls of Gram positive bacteria functions to transport and assemble of protein that capable to interact with a surrounding. These properties will enable nongenetically modified organism of Lactobacillus plantarum Pa21 to be manipulated as a carrier by anchoring externally added heterologous protein such as the AR antigens of Mycobacterium tuberculosis. To date, the protective effect of microencapsulation of Lb. plantarum Pa21 surface anchored with heterologous proteins is still unknown. The microencapsulation is believed to enhance the viability of cells in the intestine, this mechanism would also be capable to up-regulate the protection toward AR antigens anchored on Lb. plantarum Pa21 surface area. The purpose of this study is to investigate the protective effect of microencapsulation of Lb. plantarum Pa21 surface anchored with AR antigen againts simulated gastrointestinal fluid. Firstly, Lb. plantarum Pa21 without cell wall-anchored heterologous proteins were microencapsulated with different concentration of alginate and chitosan. The effect of 2% (w/v), 3% (w/v)and 4% (w/v) sodium alginate concentration coated with 0.2% w/v and 0.4% w/v chitosan concentration on the cell survival, hardness and cells released was studied. The beads produced were tested under stress conditions designed by incubation in Simulated Gastric Juice (SGF) solution at pH 1.8 followed by incubation in Simulated Intestinal Juice (SIF) solution at pH 7.45. Three percent alginate coated with 0.4 % (w/v) chitosan beads provided the best protection for Lb. plantarum in all treatments. Unencapsulated Lb. plantarum Pa21 survived the first 60 minute of the SGF solution treatment with 2.99x102 CFU/ml viable cells compared to 3% (w/v) alginate coated with0.4 % (w/v) chitosan microencapsulated cells with 6.25x108 CFU/ml viable cells after 120 minutes incubation. Secondly, a total amount of 50 μg/ml of AR protein was purified and attached to 2.19 x109 CFU/ml of Lb. plantarum Pa21. The confirmation of protein surface display was detected by SDS-PAGE and western blot before subsequently microencapsulated in 3% (w/v) alginate coated with 0.4 % (w/v) chitosan matrix. After SGF solution test, whole cell ELISA detection of microencapulated AR protein anchored to Lb. plantarum Pa21 in alginate coated chitosan has the higher value excitation of horseradish peroxide conjugate on secondary antibody compared to unencapsulated AR protein anchored to Lb plantarum Pa21. Subsequent microencapsulated AR protein anchoring to the cell wall of Lb. plantarum Pa21 also showed a microscopic excitation of FITC conjugate on secondary antibody which signified protection of microencapsulated AR protein binding on the surface of Lb. plantarum Pa21 along the GIT passage.